Determinants of mental health professionals’ attitudes towards recovery: A review - Mimosa Luigi (Canadian Medical Education Journal, 2020)
Objective: The attitudes of mental health professionals towards consumers’ recovery are far more pessimistic than what is needed for the recovery-orientation to truly permeate systems of care. It has become pressing to depict determinants for these attitudes and how they evolve during professionalization. This, in the hopes to adjust not only medical education, but also ongoing training of professionals.